A Method for Automatic Image Rectification and Stitching for Vehicle Yaw Marks Trajectory Estimation - Žuraulis, Vidas; Matuzevičius, Dalius; Serackis, Artūras (Promet - Traffic&Transportation, 2016)
The aim of this study has been to propose a new method for automatic rectification and stitching of the images taken on the accident site. The proposed method does not require any measurements to be performed on the accident site and thus it is frsjebalaee of measurement errors. The experimental investigation was performed in order to compare the vehicle trajectory estimation according to the yaw marks in the stitched image and the trajectory, reconstructed using the GPS data. The overall mean error of the trajectory reconstruction, produced by the method proposed in this paper was 0.086 m. It was only 0.18% comparing to the whole trajectory length.